2009
DOI: 10.1016/j.ijsolstr.2008.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Application of the virtual fields method to mechanical characterization of elastomeric materials

Abstract: International audienceThis paper deals with the identification of constitutive parameters of a Mooney model suitable for hyperelastic materials. These parameters are retrieved from one mechanical test that gives rise to heterogeneous stress/strain fields. Since no analytical relationship is available between measurements and unknown parameters, a suitable tool, namely the virtual fields method, is developed in case of large deformations and used to identify these unknowns. Several results obtained with numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 22 publications
3
85
0
1
Order By: Relevance
“…This stress term is expressed by the first Piola-Kirchoff stress and thus the integration domain of the PVW is based on the initial surface area of the specimen S 0 . A similar VFM has been used for static tests on rubbers [14]. The PVW of the nonlinear VFM with one of the virtual fields from Eq.…”
Section: Nonlinear Vfmmentioning
confidence: 99%
“…This stress term is expressed by the first Piola-Kirchoff stress and thus the integration domain of the PVW is based on the initial surface area of the specimen S 0 . A similar VFM has been used for static tests on rubbers [14]. The PVW of the nonlinear VFM with one of the virtual fields from Eq.…”
Section: Nonlinear Vfmmentioning
confidence: 99%
“…Such experiments provide useful tools in mechanical engineering to accurately inspect the behaviour of a material [15]. Furthermore, Promma et al [14] have found that the displacement gradient ∇u associated with such a motion shows a non-constant behaviour in space, which implies that the motion is sufficiently complex for our needs. We use the two areas of interest in Figure 1 as our images f 1 and f 2 and solve the extended optical flow problem.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…The Virtual Fields Method (VFM) is an approach dedicated to the identification of material parameters from full-field measurements [11][12][13]18]. The principle may be summarized in two steps:…”
Section: Inverse Approachmentioning
confidence: 99%
“…The choice of virtual fields was largely discussed in the literature [11][12][13]18], but only when the VFM is applied in infinitesimal deformation conditions. No rule has been established for finite deformations.…”
Section: Inverse Approachmentioning
confidence: 99%